PRACTICAL ASPECTS OF IMPLEMENTING RISK MANAGEMENT IN AGRO-INDUSTRIAL ENTERPRISES - LAGODIIENKO, Nataliia; BUNIEIEV, Ivan; KUCHUHURNYI, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article studies practical aspects of implementing risk management in agro-industrial enterprises in modern conditions.It is determined that agro-industrial production plays a strategic role in the country's economy, ensuring food security, jobs, rural development, and foreign exchange earnings.It is established that adaptive risk management in agro-industrial production is an integral part of the effective functioning of enterprises in modern conditions. Growing climatic, economic, and geopolitical threats require agribusiness to implement modern approaches to forecasting and minimizing risks.It is proven that risk management's practical implementation is based on innovative technologies, such as precision agriculture, automation of production processes, digital analysis, and monitoring systems. Financial risk management mechanisms, particularly agricultural insurance, hedging, and state compensation programs are essential.It is substantiated that adaptive strategies, particularly diversification of production, use of sustainable agricultural technologies, and optimization of logistics processes, can significantly increase a business's resilience to external challenges.It is confirmed that state support and international programs play a key role in developing effective risk management. Thanks to access to preferential financing, technological support, and educational initiatives, agro-industrial enterprises can implement more effective risk management mechanisms.Therefore, implementing an integrated approach to risk management allows agro-industrial enterprises to protect themselves from negative impacts and increase competitiveness, ensuring the stability of the agricultural sector and the country's food security.
Keywords: agro-industrial production; agro-insurance; economic development; innovative technologies; enterprise; food security; risk management